ISLAM, ETHNICITY, NATIONALISM, AND THE BURMESE ROHINGYA CRISIS - Mark Woodward (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2020)
This article discusses the world’s most oppressed people, the Muslim Rohingya of Burma (Myanmar) through the lens of “state symbologies and critical juncture”. It further argues the amalgamation of Burmese-Buddhist ethno-nationalism and anti-Muslim hate speech have become elements of Burma’s state symbology and components. Colonialism established conditions in which ethno-religious conflict could develop through policies that destroyed the civic religious pluralism characteristic of pre-colonial states. Burmese Buddhist ethno-religious nationalism is responsible for a series of communal conflicts and state repression because it did not recognize Muslims and other minorities as full and equal participants in the post-colonial national project. Therefore, the cycles of violence and the complexities of inter-ethnic and inter-religious relations indicate that Burmese political culture has become increasingly violent and genocidal.